LncRNA H19 binds VGF and promotes pNEN progression via PI3K/AKT/CREB signaling. Issue 7 (July 2019) - Ji, Meng; Yao, Yanli; Liu, Anan; Shi, Ligang; Chen, Danlei; Tang, Liang; Yang, Guang; Liang, Xing; Peng, Junfeng; Shao, Chenghao
Abstract : Pancreatic neuroendocrine neoplasms (pNENs) are endocrine tumors arising in pancreas and is the most common neuroendocrine tumors. Mounting evidence indicates lncRNA H19 could be a determinant of tumor progression. However, the expression and mechanism of H19 and the relevant genes mediated by H19 in pNENs remain undefined. Microarray analysis was conducted to identify the differentially expressed lncRNAs in pNENs. H19 expression was analyzed in 39 paired pNEN tissues by qPCR. The biological role of H19 was determined by functional experiments. RNA pulldown, mass spectroscopy and RNA immunoprecipitation were performed to confirm the interaction between H19 and VGF. RNA-seq assays were performed after knockdown H19 or VGF. H19 was significantly upregulated in pNEN tissues with malignant behaviors, and the upregulation predicted poor prognosis in pNENs. In vitro and in vivo data showed that H19 overexpression promoted tumor growth and metastasis, whereas H19 knockdown led to the opposite phenotypes. H19 interacted with VGF, which was significantly upregulated in pNENs, and higher VGF expression was markedly related to poor differentiation and advanced stage. Furthermore, VGF was downregulated when H19 was knocked down, and VGF promoted cell proliferation, migration and invasion. Mechanistic investigations revealed that H19 activated PI3K/AKT/CREB signaling and promoted pNEN progression by interacting with VGF. These findings indicate that H19 is a promising prognostic factor in pNENs with malignant behaviors and functions as an oncogene via the VGF-mediated PI3K/AKT/CREB pathway. In addition, our study implies that VGF may also serve as a candidate prognostic biomarker and therapeutic target in pNENs.